Ortner’s syndrome: Cardiovocal syndrome caused by aortic arch pseudoaneurysm - Al Kindi, Adil H. (J Saudi Heart Assoc, 2016)
72-year-old hypertensive presented with two weeks history of left sided chest pain and hoarseness. Workup demonstrated a pseudoaneurysm in the lesser curvature of the distal aortic arch opposite the origin of the left subclavian artery from a penetrating atherosclerotic ulcer. Following a left carotid-subclavian bypass, endovascular stenting of the aorta was performed excluding the pseudoaneurysm. Patient had excellent angiographic results post-stenting. Follow up at 12 weeks demonstrated complete resolution of his symptoms and good stent position with no endo-leak. Ortner’s syndrome describes vocal changes caused by cardiovascular pathology. It should be included in the differential diagnosis of patients with cardiovascular risk factors presenting with hoarseness. This case demonstrates the use of endovascular stents to treat the causative pathology with resolution of symptoms. In expert hands, it represents low risk, minimally invasive therapeutic strategy with excellent early results in patients who are high risk for open procedure.